Respostas

2013-09-10T18:01:58-03:00
4x-10=2x+2
4x-2x = 2+10
2x = 12
x = 12/2
x = 6

4x-7=8x-2
4x-8x = -2+7
-4x = 5(-1)
4x = -5
x = -5/4

4x-1=3(x-1)
4x -1 = 3x-1
4x-3x = -1+1
x = 0

2(x-1)=3x+4
2x-2 = 3x+4
2x-3x = 4+2
-x = 6(-1)
x = -6

3(x-1)-7=15
3x-3-7 = 15
3x = 15+3+7
3x = 25
x = 25/3

7(x-4)=2x-3
7x-28 = 2x-3
7x-2x = -3+28
5x = 25
x = 25/5
x = 5

3(x-2)=4(3-x)
3x-6 = 12-4x
3x+4x = 12+6
7x = 18
x = 18/7


3(3x-1)=2(3x+2)
9x-3 = 6x+4
9x-6x = 4+3
3x = 7
x = 7/3


7(x-2)=5(x+3)
7x-14 = 5x+15
7x -5x = 15+14
2x = 29
x = 29/2



5x-3(x+2)=15
5x-3x-6 = 15
5x-3x = 15+6
2x = 21
x = 21/2

2x+3x+9=8(6-x)
2x+3x+9 = 48-8x
2x+3x+8x = 48-9
13x = 39
x = 39/13
x = 3
1 5 1